Dendritic cell-based immunotherapy in non-small cell lung cancer: a comprehensive critical review - Oliveira, Jamile Barboza de; Silva, Saulo Brito; Fernandes, Igor Lima; Batah, Sabrina Setembre; Herrera, Andrea Jazel Rodriguez; Cetlin, Andrea de Cássia Vernier Antunes; Fabro, Alexandre Todorovic (Frontiers in Immunology, 2024)
Despite treatment advances through immunotherapies, including anti-PD-1/PD-L1 therapies, the overall prognosis of non-small cell lung cancer (NSCLC) patients remains poor, underscoring the need for novel approaches that offer long-term clinical benefit. This review examined the literature on the subject over the past 20 years to provide an update on the evolving landscape of dendritic cell-based immunotherapy to treat NSCLC, highlighting the crucial role of dendritic cells (DCs) in immune response initiation and regulation. These cells encompass heterogeneous subsets like cDC1s, cDC2s, and pDCs, capable of shaping antigen presentation and influencing T cell activation through the balance between the Th1, Th2, and Th17 profiles and the activation of regulatory T lymphocytes (Treg). The intricate interaction between DC subsets and the high density of intratumoral mature DCs shapes tumor-specific immune responses and impacts therapeutic outcomes. DC-based immunotherapy shows promise in overcoming immune resistance in NSCLC treatment. This article review provides an update on key clinical trial results, forming the basis for future studies to characterize the role of different types of DCs in situ and in combination with different therapies, including DC vaccines.